Influence of government investment and private investment and labor against domestic product gross regional and own local revenue samarinda - Andi Abdul Wahab; Rusdiah Iskandar; Irwansyah Irwansyah (Faculty of Economics and Business Mulawarman University, 2016)
This study aimed to examine the influence of direct and indirect Government Investment and Private Investment and Labor against the Gross Domestic Product and Local Revenue Samarinda. Engineering analysis to determine the effect of independent variables on the dependent variable used path analysis tool (Path analysis) with decomposition model is done through the statistical program SPSS. The study states (1) The Government Investment no significant effect on the GDP amounted to (0.050.538). (2) Private Investment significant effect on the GDP amounted to (0.050.041). (3) Labor significant effect on the GDP amounted to (0.050.001). (4) The Government Investment no significant effect on revenue of (0.050.095). (5) Private investment no significant effect on Local Own Revenue (0.05 0.146). (6) Labor no significant effect on Local Own Revenue (0.050.954). (7) GDRP no significant effect on Local Own Revenue (0.05 0.130). (8) Directly Government Investment Local Own Revenue positive influence in the formation of which is equal to 0.075, while the indirect effect of the Government Investment to the Local Own Revenue through the GDRP of (0.075 x 0.618 = 0.046). (9) The Private Investment also has a positive effect but not significant to the revenue of 0.289. The indirect effect of Private Investment to the Local Own Revenue through the GDRP amounted to (0.289 x 0.618 = 0.179). (10) The results of the analysis of Labor positive but not significant influence 0,023 to the GDRP formation, while the indirect effect of Labor to the Local Own Revenue through the GDRP amounted to (0.711 x 0.618 = 0.439).Keywords: Government Investment, Private Investment, Labor, Gross Domestic Regional of Product, Own Local Revenue.